2014
DOI: 10.1590/1808-057x201410820
|View full text |Cite
|
Sign up to set email alerts
|

The Causes of Fiscal Transparency: Evidence in the Brazilian States

Abstract: The transparency of governments to their citizens is seen as a necessary factor in democratic accountability and, consequently, in the consolidation of democracy. Although the importance of transparency in government is often highlighted, its causes are still unknown, especially in the Brazilian context. Following the trend of international empirical research, this exploratory study investigates the relationships between three sets of variables (current and past fiscal variables, socioeconomic variables and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 21 publications
2
9
0
11
Order By: Relevance
“…Among the individuals who answered "yes, " the proportion of dishonest ones was 62.1%, while for those who answered "no, " the proportion was 22.1%; for "don't know" it was 33.3%. These results are consistent with previous findings (Ellis & Fender, 2003;Feld & Frey, 2007;Pickhardt & Prinz, 2014;Zuccolotto & Teixeira, 2014). Such behavior is reflected in dishonesty according to the trust generated in the individual through the actions of the institutions (Kogler et al, 2013).…”
Section: Influence Of Internal Rewardssupporting
confidence: 93%
See 1 more Smart Citation
“…Among the individuals who answered "yes, " the proportion of dishonest ones was 62.1%, while for those who answered "no, " the proportion was 22.1%; for "don't know" it was 33.3%. These results are consistent with previous findings (Ellis & Fender, 2003;Feld & Frey, 2007;Pickhardt & Prinz, 2014;Zuccolotto & Teixeira, 2014). Such behavior is reflected in dishonesty according to the trust generated in the individual through the actions of the institutions (Kogler et al, 2013).…”
Section: Influence Of Internal Rewardssupporting
confidence: 93%
“…Ellis and Fender (2003) analyzed the corruption and transparency variables with an emphasis on the government's behavior and found that the higher a country's level of fiscal transparency, the lower the percentage of corruption. Corroborating with these results, Zuccolotto and Teixeira (2014) carried out a study in Brazilian states to discover the causes of fiscal transparency. The authors found that these causes are associated with better socioeconomic and human development, with a high level of competition, and with a low level of corruption.…”
Section: Internal Rewardsmentioning
confidence: 95%
“…Essas perspectivas foram definidas por esses autores levando-se em consideração trabalhos realizados pela Transparência Internacional, pelo International Budget Partnership e por trabalhos que se dedicaram a avaliar os níveis de transparência, tanto no contexto nacional, como no internacional, como (CRUZ et al, 2012;PINHO, 2008;TEIXEIRA, 2014).…”
Section: As Diversas Perspectivas Analíticas Da Transparênciaunclassified
“…Trabalhos realizados no Brasil (AKUTSU; PINHO, 2002;CRUZ et al, 2012;PINHO, 2008;TEIXEIRA, 2014) se propuseram 1 O termo estilizado, na concepção utilizada por Michener e Bersch (2011), sugere que o termo transparência é modificado (suprimindo-se, substituindo-se e/ou acrescentando elementos ao termo) para que seja possível obter determinados resultados. 2 Transparência midiática refere-se, neste trabalho, às informações divulgadas em meio eletrônico de acesso público como portais e sites na internet.…”
Section: Introductionunclassified
“…No entanto, mesmo que tais leis estabeleçam conteúdos orçamentários mínimos, a serem divulgados pelos entes subnacionais, e em virtude da importância atribuída à transparência como princípio para a democratização do Estado, diversas pesquisas revelam a existência de deficit de transparência orçamentária na gestão pública (e, consequentemente, de democracia), independentemente do nível governamental considerado (AKUTSU; PINHO, 2002;INESC, 2001;ZUCCOLOTTO, 2014;SANTANA JUNIOR, 2008;ZUCCOLOTTO;TEIXEIRA, 2014). Essas pesquisas apontam, ainda, que o nível de transparência é diferente entre os estados subnacionais e entre os municípios.…”
unclassified